Vesicular - Arbuscular Mycorridzae of Casuarina Equisetifolia forst. in Four Different Soil Types in Tamil Nadu - Sambandan, K.; Kannan, K.; Raman, N. (Indian Forester, 1994)
Mycorrhizal association in Casuarina equisetifolia grown in four different soil types, namely sandy loam soil, red soil, clay soil and sandy soil was inveastigated. The plants from all four sites were found to Possess hyphae, vesicles and arbuscles in their roots. The four types of soil were nitrogen deficient but rich in phosphorus and potassium and soils were acidic to alkaline. The rhizosphere soils harboured Spores of different VAM fungi and diversity of spore types were observed in all four site. A total of 10 species of Glomus, 2 ofGigaspora and 2 of Sclerocystic In the rhizosphere soils were recorded. In four sites, variation in per cent root colonization and number of spores per 100g of soil were noted.